Locally aggressive trichilemmal carcinoma - Ana María Maya-Rico; Catalina Jaramillo-Pulgarín; Ángela Londoño-García; Bibiana Peña-Zúñiga (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Trichilemmal carcinoma is a rare adnexal neoplasia with histologic features reminiscent of the outer root sheath of hair follicles. The clinical presentation of trichilemmal carcinoma is variable, as it may mimic basal cell carcinomas and squamous cell carcinomas, thus requiring histologic diagnosis. We report the case of a patient with aggressive trichilemmal carcinoma in the auricle.